La gestión administrativa en la Institución Conagopare, provincia de Cotopaxi, cantón Latacunga periodo 2023 - Molina Altamirano, María Fernanda (2023)
This research work was developed with the objective of diagnosing the Administrative Management in CONAGOPARE Province of Cotopaxi, Canton Latacunga. Administrative management is not a topic that should be taken lightly, since effective management will help the institution in the execution of various activities aimed at coordinating all available resources to comply with the established objectives. One of the main purposes of the research is to collaborate in the gradual and successful improvement of the Administrative Management of CONAGOPARE Cotopaxi. Based on important factors taken from various theories and scientific thoughts of authors with knowledge on the subject, for this reason the methodology used has a quantitative approach, with a non-experimental design and applying cross-sectional studies, in addition to an explanatory and field research. We also applied the survey technique and its instrument called questionnaire, applied to the 10 employees of the institution, the instrument in question is made up of 23 questions based on administrative management, it is also divided into 5 dimensions that establish planning, organization, direction, control and management. The questionnaire helped us to gather precise information on the current state of the organization. In the results of the situational diagnosis it was identified that the Administrative Management of CONAGOPARE Cotopaxi presented a series of deficiencies, for example: low participation of the collaborators in the elaboration of plans and projects of the institution with 30% of negative results, on the other hand it was detected the lack of recognition for work performance with 50% of negativity, in addition it was identified that there is little use of tools for decision making according to 40% of results and finally it was determined the lack of productivity in problem solving with 40% of unfavorable results, This was a great reason to direct the research proposal that focused on the development of strategies for the improvement of administrative management in the institution CONAGOPARE Cotopaxi, within the strategies provided we find the promotion of effective communication, incorporate recognition for job performance, improve decision making and improvement in the management of CONAGOPARE Cotopaxi, it should be noted that each of the proposed strategies are made up of activities, participants, times and respective costs for future implementation. It is also valid to note that the implementation of the proposed strategies will generate economic xi impacts, since the implementation of the proposed strategies will require a considerable economic investment for greater effectiveness; on the other hand, the technical impact generated in the collaborators will also be notable, since the work team will have to adapt to new techniques, knowledge and requirements of the institution. It should also be noted that the beneficiaries will be the internal and external collaborators of the organization. For this reason, it is important to state that this study will contribute to the generation of new knowledge for the professionals of the institution, as well as for future research.